MMSE detection method in uplink massive MIMO systems based on quantum computing - Wang, XiaoJun; Zhao, Jie; Meng, FanXu; Yu, XuTao; Zhang, ZaiChen (Physics letters. A, 2019)
The minimum mean square error (MMSE) detection method involved matrix inversion operation with excessive computational burden. In this paper, we develop an improved quantum linear system algorithm to solve matrix inversion problem of the MMSE detection method in uplink massive multiple-input and multiple-output (MIMO) systems. In order to apply reasonably the robust computational power of quantum computing, we optimize the preparation of the input state and the extraction of the solution from the final entangled quantum state. We prove that this algorithm can reduce computational complexity to O(Nlog⁡N). •This quantum algorithm reduced the complexity about the matrix inversion.•This paper combined massive MIMO systems with quantum computing.•Preparing a quantum state to substitute for a classical input state.•A readout approach is applied to obtain the solution from entangled quantum state.